Bahasa Tubuh dan Perilaku Kaum Penyimpang Seksual dalam Film Perfect Strangers: (Analisis Semiotika John Fiske) - Pramonojati, Twin Agus (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
The phenomenon of LGBT behavior in Indonesia today is not only focused on community associations but has also become a vigorous movement of ideology and real action. LGBT is a form of sexual orientation deviation committed by a person who loves each other with the same sex. Currently, LGBT people in Indonesia have dared to show themselves openly through social media digital platforms, and other mass media. Film as one of the mass media also raises topics related to LGBT, one of which is a film entitled 'Perfect Stranger' which indicates the body language and behavior of one of the characters named Tomo which leads to homosexuals (gay). The purpose of this research is to find out how the body language and behavior of sexual deviants, especially gays, interact and communicate with those closest to them so that people can anticipate their further involvement in socializing. The method in this research is qualitative, with John Fiske's semiotic analysis approach consisting of three levels, namely the level of reality, representation, and ideology. The results show that there is body language and behavior of sexual deviants shown by Tomo's character who acts as a gay individual. The reality of body language is shown in the form of hugging, embracing hips, limp wrists, and waving. In addition, it is also represented through the characteristics of the costumes used. At the level of representation, the movie uses a lot of medium shots and J&L cut techniques that focus on strengthening Tomo's character as gay. The ideology concluded in Perfect Strangers is the ideology of liberalism